Resolving the term “offshore aquaculture” by decoupling “exposed” and “distance from the coast” - Buck, Bela H.; Bjelland, Hans V.; Bockus, Abigail; Chambers, Michael; Costa-Pierce, Barry Antonio; Dewhurst, Tobias; Ferreira, Joao G.; Føre, Heidi Moe; Fredriksson, David W.; Goseberg, Nils; Holmyard, John; Isbert, Wolf; et al. (Frontiers in Aquaculture, 2024)
The terms "offshore" and "open ocean" have been used to describe aquaculture sites that are further from the coast or in higher energy environments. Neither term has been clearly defined in the scientific literature nor in a legal context, and the terms are often used interchangeably. These and other related terms (for example "exposed", "high-energy") variously refer to aspects of a site such as the geographic distance from shore or infrastructure, the level of exposure to large waves and strong currents, the geographic fetch, the water depth, or some combination of these parameters. PAGE \* Arabic \* MERGEFORMAT 3 Key differences and the importance of these terms are discussed that affect various interest groups. Follow-up articles in this compilation from scientific members of the WGOOA as well as other scientists outside ICES are incorporated that develop a set of definitions and a rigorous exposure index.